ENDOBRONCHIAL SANITATION IN THE TREATMENT OF PATIENTS WITH PULMONARY ABSCESS COMPLICATED BRONCHIAL FISTULA (Archive of Conferences, 2020)
Analysis of the research data of a number of authors show that the percentage of development of pulmonary-pleural complications in lung abscesses ranges from 30 to 70%, and the incidence of gangrenous forms from 28 to 74% [Bisenkov LN, Okhunov AO]. The level of mortality remains high, making up, in general, with various forms of purulent-necrotic process from 12.7% to 77.8% [Geller D.B., Gostishchev V.K. and etc.]. The formation of a bronchial fistula with a lung abscess is the most common complication of a lung abscess